THE ROLE OF LEPTIN IN REPRODUCTIVE FUNCTION: INSIGHTS INTO ITS EFFECTS ON MENSTRUAL CYCLE REGULATION AND FERTILITY IN WOMEN - Jawad Hussain Qamber; Saadia Sajjad; RidaAjmal Khan; Maryam Anwar; Shahid Latif; Mussarat Bano (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Leptin, primarily known for its role in appetite regulation, has emerged as a key player in reproductive health. Leptin has long been known to have metabolic effects, but it also affects men's and women's reproductive systems. It is very desirable to comprehend its effects on female reproductive function, specifically on the control of the menstrual cycle and fertility.Research Objective: The objective of this research was to investigate the role of leptin in reproductive function, particularly focusing on its impact on menstrual cycle regulation and fertility in women.Methodology: A prospective observational study was conducted over a period of six months at the Department of Obstetrics and Gynaecology, Services Hospital, Lahore - Pakistan. A sample size of 58 participants was determined through power analysis calculations. Assessments were done on leptin levels, reproductive hormones, normal menstrual cycles, baseline features, and fertility results. To investigate relationships between variables, statistical methods included regression analysis, correlation analysis, and descriptive statistics.Results: In our study of 58 participants, we found that leptin levels decreased significantly from the follicular phase (12.40 ng/mL ± 3.10) to the luteal phase (9.80 ng/mL ± 2.50), while other reproductive hormones showed delicate fluctuations. Most participants had regular menstrual cycles (n=48; 82.80%), with 69.12% (n=40) achieving successful conception. Leptin levels were positively correlated with LH, FSH, estrogen, and progesterone. Regression analysis revealed leptin as a significant predictor for irregular menstrual cycles (β = 0.27, p < 0.05) and fertility outcomes (β = 0.35, p < 0.01), while other factors like age, BMI, smoking, and alcohol consumption had negligible effects.Conclusion: Our study emphasizes leptin's role in female reproductive function, impacting menstrual cycles and fertility, urging tailored interventions for optimal outcomes.